PENDIDIKAN ISLAM MULTIKULTURAL SEBAGAI WADAH IMPLEMENTASI TOLERANSI DAN KEBHINEKAAN DI SEKOLAH DASAR - Harahap, Sery Bulan; Fata, Nahriyah (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This study aims to to examine the concept of multicultural Islamic education and its implementation as a means of instilling the values of tolerance and diversity in elementary schools. In the context of Indonesia’s pluralistic society, primary education plays a strategic role in shaping children's character to respect cultural, religious, and ethnic differences. This research employs a library research method with a descriptive qualitative approach, reviewing various academic sources on Islamic education, multiculturalism, and character education. The findings reveal that multicultural Islamic education can instill tolerance values through the integration of inclusive and peace-oriented Islamic teachings, as well as through learning activities that emphasize appreciation of diversity. Implementation of this approach can be carried out through teacher role modeling, intercultural activities, and curricula that uphold pluralism. Multicultural Islamic education has proven effective in shaping students who are tolerant, inclusive, and capable of living harmoniously in a diverse society.